HUBUNGAN ANTARA HEPATOTOKSISITAS DENGAN USIA, STATUS GIZI, DAN LAMA PEMBERIAN ASAM VALPROAT PADA ANAK EPILEPSI - , Siti Aurelia Nurmalasari, Dr. dr. E.S. Herini., Sp AK ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Epilepsy is still a disease that affects many people all around the world with an estimated 50 million people suffer from epilepsy. The annual incidence rate ranges from 20-70 cases per 100,000 population and the prevalence rate from 0.4 to 0.8 percent. The high prevalence of epilepsy will directly impact on the high use of valproic acid in children and this may increase the risk of hepatotoxicity. The aim of this study is to investigate the relationship between the age, nutritional status, duration of therapy and hepatotoxicity in epileptic children who received valproic acid. This is a cross-sectional study. The data taken in September-November 2011 in the department of pediatric neurology of DR. Sardjito Hospital Yogyakarta. The inclusion criteria were children with epilepsy aged < 18 years who received valproic acid therapy for at least 3 months as outpatient who willing to follow the study. Exclusion criteria were children with no previous liver disease. Data processed using Pearson and Spearman correlation. This study showed no association between age of patient and hepatotoxicity in children with epilepsy using valproic acid (r = - 0.009, p = 0.946). Other factors that were tested showed no association between duration of therapy, nutritional status and hepatotoxicity (r = 0.009, p = 0.947 and r = -0.198, p = 0.136 irrespectively). The age of patient, nutritional status, duration of therapy are not associated with hepatotoxicity in children with epilepsy who received valproic acid.